'I've got a little list'—the scourge of a surgical junior. A quality improvement project to change the surgical patient list in a district general hospital. Issue 2 (15th June 2020) - Khan, Hiba; Flesher, Elizabeth; Marshman, James; Harding, Alexander; Bethune, Rob; Lawday, Samuel
Abstract : Background: Junior doctors at the Royal Devon and Exeter Hospital spend hours every day creating and updating patient lists for all surgical specialties on Microsoft Excel spreadsheets. This not only consumes time that should be spent on clinical tasks, it allows for human errors, system errors and patient safety concerns. Our aim was to reduce time spent on the list and reduce the chance for error. Methods: We measured the time junior doctors spent creating and updating the surgical lists for one specialty, and on-call shifts. Our first Plan-Do-Study-Act (PDSA) cycle was to introduce clinical secretaries; this reduced the time spent by ward teams on the list but had no effect on the on-call team. We then worked with the hospital application developer to adapt software currently used to suit all surgical teams. Once completed, this software was rolled out alongside the existing spreadsheet method with a view to a switch after a transition period. Results: The introduction of clinical secretaries reduced the time spent on the colorectal surgery list from 99.22 min a day to 43.38 min. The on-call team however did not benefit from this intervention. Following the introduction of the new software, the day on-call team time spent on the list changed from 121 min a day to 4.66 min. The night on-call team time changed from 91 min to 7.38 min. Conclusion: Reducing the time juniors spend compiling surgical lists has clear benefits to patients with extra time for junior doctors to clerk patients. The use of an automated system removes the chance of error in transcription of blood results. Due to the success of this project, colorectal, upper gastrointestinal, urology, vascular and on-call teams have adopted the new list permanently.